Pengaruh Free Cash Flow dan Operating Cash Flow terhadap Kebijakan Deviden dengan Profitabilitas Sebagai Variabel Intervening : Pada Perusahaan Manufaktur Food And Beverage yang Terdaftar di BEI Periode 2021 – 2023 - Herlina Suistiyaningsih; Rodhiyah Rodhiyah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine and analyze the influence of free cash flow and operating cash flow on dividend policy through profitability as an intervening variable. This study used a sample of 22 food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX), which consistently published annual reports and distributed dividends from 2021 to 2023. The study used a quantitative approach, using multiple linear regression and path analysis to test the proposed hypotheses. The analysis results indicate that, partially, operating cash flow and profitability exhibit a positive and significant influence on dividend policy, while free cash flow has no significant influence on dividend policy. Furthermore, free cash flow and operating cash flow individually have no effect on profitability. Based on the path analysis, profitability is found to act as a mediating variable in the relationship between free cash flow and operating cash flow on dividend policy